Influence of geometric parameters on perforated core buckling restrained braces behavior - Hashem Jahangir (Iranian Society of Structrual Engineering (ISSE), 2019)
Buckling Restrained Braces (BRBs) are installed in buildings to control lateral displacements caused by seismic events. Although, conventional BRBs have various advantages comparing to ordinary bracing systems, their high weight and dimensions because of the restraining units is a dominant drawback. In this paper, a new developed type of BRB named perforated core buckling restrained brace is investigated which resolved conventional BRBs shortcoming. Its core consists of a perforated steel yielding plate which is guided and partially stabilized by the restraining unit. The core is mechanized to obtain two yielding lateral bands which are connected by several equidistant stabilizing bridges. At first part of the paper, the hysteretic behaviour of the tested braces and a large scale brace has been analysed and verified with an FEM model which considers the interaction between the core and the encasing member. The model reproduces the hysteretic response during the first cycles and the influence of friction on the axial strain distribution along the yielding core. In the second part, geometrical parameters such as number of holes and their section in the core of brace were studied and trough hysteretic behaviour, stress distribution, core deformation and its condition under ultimate loads, the optimized core is selected and suggested.